Mixtec Foodways in Achiutla: Continuity Through Time. A Paleoethnobotanical Study Comparing the Postclassic and Early Colonial Diet - Bérubé, Éloi (My University, 2017)
Numerous historical reports written by Spaniards in the Americas during the Early Colonial Period describe public life. However, less is known about quotidian lives during this period. In the Mexican state of Oaxaca, a region encompassing dozens of cultural groups, little is known about the everyday life of Mixtecs and how they reacted towards the newly established Spanish authority in their households. When they arrived at Achiutla, one of the biggest religious centres of ancient Oaxaca (Byland 2008), the Spaniards imposed their power on the public sphere, using religion and economy amongst others (Terraciano 2001:294, 340). My objective is to study the Mixtecs’ reaction to the arrival of Spaniards in the region by using paleoethnobotany to study foodways and how Achiutla’s inhabitants negotiated the arrival of new food items and to what level they accepted, incorporated, and resisted them. This study presents the traditional Mixtec and Spanish foodways and the important role they played in their beliefs, traditions, and identities. I present elements supporting the claim that certain Spaniards might have tried to modify Indigenous foodways in the Americas, while others believed it was preferable for Spaniards and Indigenous people to eat different foods. This study also presents other results obtained in Colonial foodways studies made in the Americas and in the Mixteca Alta region. This study includes the analysis of 27 paleoethnobotanical samples, 22 of them being macrobotanical remains obtained from light fractions and 5 of them coming from microbotanical residues extracted from artifacts. All these samples were collected by Jamie Forde in 2013 at San Miguel Achiutla in the course of the PASMA archaeological project and come mainly from two terraces (10 and 13) likely occupied by Mixtec nobility. By combining samples coming from the Postclassic and the Early Colonial Periods, this study establishes the Mixtec diet prior to the arrival of Europeans in the region, enabling a better comparison between the two. This study supports the idea that the Mixtec diet likely remained the same at Terraces 10 and 13 during the Postclassic and the Early Colonial Periods. Two genera dominate the paleoethnobotanical assemblage: Chenopodium sp. (pazote, apazote) and Amaranthus sp. (huisquelite or quelite), the presence of which demonstrates continuity through times. I assess different scenarios that might explain the absence of European introduced plant species at Achiutla, cautiously presenting a hypothesis linked to Mixtec colonial resistance.
Keywords: Foodways, paleoethnobotany, archaeology, Mixtecs, Oaxaca, Colonial Period